The Influence of Live Streaming and Twin Date Promotion on Consumer Purchase Decision for Skintific Products on TikTok Shop (a Study Among Students in Pontianak City) - Rahmawati, Ananda Putri; Archie, Ananda (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to analyze the influence of live streaming and twin date promotion on the purchase decision of Skintific products on TikTok Shop among college students in Pontianak City. With the rapid development of e-commerce and the online shopping trend, TikTok Shop has become an attractive platform for many consumers, especially among the younger generation. The phenomenon of live streaming as an interactive promotional tool and twin date promotions offering attractive discounts have become unique attractions for consumers in making purchasing decisions. The method used in this study is a quantitative method with an associative approach. Data was collected using a questionnaire distributed to 100 respondents who met the research criteria. Instrument testing was conducted using validity and reliability tests using SPSS, with results indicating that all instruments used in this study were valid and reliable. The classical assumption tests included normality, linearity, and multicollinearity tests, which showed that the data met the requirements for multiple linear regression analysis. The results of the f-test (simultaneous) showed that live streaming and twin date promotions had a simultaneous effect on purchasing decisions. The partial test showed that both independent variables, namely live streaming and twin date promotions, had a significant effect on purchasing decisions. The coefficient of determination (R²) of 0.200 indicates that 20% of the variation in purchase decisions can be explained by these two variables, while the remaining 80% is influenced by other factors not examined in this study. These findings provide insights for TikTok Shop and brands like Skintific to optimize live streaming features and design more appealing promotions to enhance purchase decisions among consumers.